(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2025)
This project compares the Relational Database model with the Semantic Web Ontology model through an educational web application serving academic levels in Libya from primary to secondary school. The application illustrates key differences in data storage and retrieval between the two models. Developed using software engineering principles, the system emphasizes flexibility, scalability, reliability, and usability. It manages educational entities—students, teachers, curricula, institutions, and their locations—by efficiently representing them and their relationships in both models. Practical comparisons showed that the Semantic Web Ontology offers superior flexibility and semantic representation, with faster search and reasoning capabilities that reveal new relationships. However, it needs improvements in security and reliability.